2014
DOI: 10.1097/rhu.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Polyarthritis and Pancreatic Panniculitis Associated With Pancreatic Carcinoma

Abstract: Pancreatic disorders, such as chronic or acute pancreatitis, and carcinoma may be infrequently accompanied or preceded by panniculitis or polyarthritis. This triad is known in the literature as the pancreatitis, panniculitis, and polyarthritis syndrome. Although the pancreatic disease of pancreatitis, panniculitis, and polyarthritis syndrome usually includes pancreatitis, here we review the literature with report of 1 additional case of polyarthritis and panniculitis occurring in the presence of pancreatic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 38 publications
0
39
0
5
Order By: Relevance
“…The underlying pancreatic disease is either acute or chronic pancreatitis [1]. Previous reports have shown that a pancreatic mass, such as a pseudopapillary pancreatic tumor, a malignancy (composed of acinar cell types), or a pancreatic pseudocyst, can also cause PPP syndrome [4][5][6][18][19][20]. Our patient had acute pancreatitis, subcutaneous fat necrosis, and polyarthritis, including medullary fat necrosis.…”
Section: Discussionmentioning
confidence: 79%
“…The underlying pancreatic disease is either acute or chronic pancreatitis [1]. Previous reports have shown that a pancreatic mass, such as a pseudopapillary pancreatic tumor, a malignancy (composed of acinar cell types), or a pancreatic pseudocyst, can also cause PPP syndrome [4][5][6][18][19][20]. Our patient had acute pancreatitis, subcutaneous fat necrosis, and polyarthritis, including medullary fat necrosis.…”
Section: Discussionmentioning
confidence: 79%
“…PPP syndrome has been described following multiple causes of pancreatic damage, including trauma,7 acute and chronic inflammatory conditions of the pancreas,4 8 and malignancy 9. These conditions are known to cause elevated levels of serum pancreatic enzymes, and yet commonly patients with pancreatitis or raised amylase levels do not always exhibit cutaneous or orthopaedic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Men are predominantly affected, with a mean age at diagnosis of 61 years 20 . The diagnosis is made based on a deep biopsy (including subcutaneous adipose tissue), showing lobular panniculitis with liquefactive necrosis and anucleate adipocytes (‘ghost cells’).…”
Section: Pancreatic Panniculitismentioning
confidence: 99%
“…The clinical course depends on the underlying disorder. Especially in paraneoplastic cases, the condition runs a prolonged course and is associated with a poor overall prognosis, with mortality rates of up to 74 % 20 . Differential diagnoses to be ruled out include other forms of panniculitis such as erythema nodosum, erythema induratum, lupus panniculitis and subcutaneous panniculitis‐like T‐cell lymphoma.…”
Section: Pancreatic Panniculitismentioning
confidence: 99%